Pulse oximeter signal analysis in exercise environments - Chan, Hui Ying. (2013)
Pulse Oximeter, a non-invasive measurement of arterial oxygen saturation, is widely acknowledged to be one of the most important technological advances in monitoring clinical patients. Pulse oximeter computes SpO2 by measuring the differences in the visible and infrared absorbance of fully oxygenated and deoxygenate arterial blood. It also provides continuous, safe and instantaneous measurement of blood oxygenation.